2013
DOI: 10.1590/s0100-06832013000100018
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum in corn plants: influence on growth and morpho-anatomy of root and leaf

Abstract: Aluminum (Al) toxicity is one of the most limiting factors for productivity. This research was carried out to assess the influence of Al nutrient solution on plant height, dry weight and morphoanatomical alterations in corn (Zea mays L.) roots and leaves. The experiment was conducted in a greenhouse with five treatments consisting of Al doses (0, 25, 75, 150, and 300 µmol L-1) and six replications. The solutions were constantly aerated, and the pH was initially adjusted to 4.3. The shoot dry matter, root dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
2
23
0
3
Order By: Relevance
“…On the other hand, in 300 µM Al-treated root, the diameter of metaxylem vessels was increased (Plates 2 and 3). Similarly, due to 300 µM L -1 Al, Batista et al (2012) found that, in the vascular bundle, the metaxylem and protoxylem had no secondary walls and their diameter was much smaller compared to that of control plants. This study demonstrated that higher concentration of Al caused structural impairment.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, in 300 µM Al-treated root, the diameter of metaxylem vessels was increased (Plates 2 and 3). Similarly, due to 300 µM L -1 Al, Batista et al (2012) found that, in the vascular bundle, the metaxylem and protoxylem had no secondary walls and their diameter was much smaller compared to that of control plants. This study demonstrated that higher concentration of Al caused structural impairment.…”
Section: Resultsmentioning
confidence: 93%
“…In Al-treated root, the cortical cells presented a higher amount of intercellular space and its cells were elongated longitudinally (Plates 2 and 4). According to Batista et al (2012), due to 75 and 300 µmol L -1 Al treatment in maize root, the cortical parenchyma cells consisted of prominent intercellular spaces, which was a form of adaptation. Sclerenchymatous layer was uniserate both in control and 150 µM Al treated plant but biseriate in 300 µM Al-treated plant (Plate 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the limitation on nutrient absorption by plants when Al was present in the soil at toxic levels. The main symptom of Al toxicity in differents plants was rapid root growth inhibition caused by different mechanisms, such as interactions of Al 3+ with the cell wall and plasma membrane, callose production, and damage to the apoplast (MA et al, 2004, BATISTA et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30% of the world's soils are classified as acidic (FAO, 2015), while more than 50% of the agricultural land is acidic (pH ≤ 5.5). The Al +3 ions absorbed by plants are predominantly present in their root systems because they perform their growth inhibitory function in the root elongation zone (Batista et al, 2013). Aluminum may interfere with the polar transport of auxins, mainly affecting the formation of lateral roots that are important for nutrient uptake.…”
Section: Plant Growthmentioning
confidence: 99%